12n+2(n-3)=1+5(2n-1)

Simple and best practice solution for 12n+2(n-3)=1+5(2n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12n+2(n-3)=1+5(2n-1) equation:


Simplifying
12n + 2(n + -3) = 1 + 5(2n + -1)

Reorder the terms:
12n + 2(-3 + n) = 1 + 5(2n + -1)
12n + (-3 * 2 + n * 2) = 1 + 5(2n + -1)
12n + (-6 + 2n) = 1 + 5(2n + -1)

Reorder the terms:
-6 + 12n + 2n = 1 + 5(2n + -1)

Combine like terms: 12n + 2n = 14n
-6 + 14n = 1 + 5(2n + -1)

Reorder the terms:
-6 + 14n = 1 + 5(-1 + 2n)
-6 + 14n = 1 + (-1 * 5 + 2n * 5)
-6 + 14n = 1 + (-5 + 10n)

Combine like terms: 1 + -5 = -4
-6 + 14n = -4 + 10n

Solving
-6 + 14n = -4 + 10n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-10n' to each side of the equation.
-6 + 14n + -10n = -4 + 10n + -10n

Combine like terms: 14n + -10n = 4n
-6 + 4n = -4 + 10n + -10n

Combine like terms: 10n + -10n = 0
-6 + 4n = -4 + 0
-6 + 4n = -4

Add '6' to each side of the equation.
-6 + 6 + 4n = -4 + 6

Combine like terms: -6 + 6 = 0
0 + 4n = -4 + 6
4n = -4 + 6

Combine like terms: -4 + 6 = 2
4n = 2

Divide each side by '4'.
n = 0.5

Simplifying
n = 0.5

See similar equations:

| 12x+11y=18 | | 4b+3-b=4(b-5)+2 | | 0.4(p+1)-0.9(p+5)=-2 | | (2x^2+3x-6)-(x^2-18x+6)= | | -250+5(5)= | | 6(7x+9)=264 | | 6(3+k)=48 | | c-(-75)=25 | | -250+5(3)= | | 4(h+8)=16 | | 6-4u=2 | | a(6a^2+2a+9)= | | 6(2-x)=20 | | 21-11y=7 | | 2x-10(2x-1)=5 | | 0.5x+58=-23 | | 7y=210 | | -6x-7=29 | | 250=x*1000 | | 6x+2x-5=43 | | (X-3)(X+3)=6x^2-14 | | 5+3(4x-2)=-18 | | a+7=11 | | 16R+4R+80=X | | -2x^4(6x^3-5x+5)= | | 790=7.5x+(197.5+(-1.875x)) | | 9+2(b-8)=9(-3-2b) | | 5p=16-3p | | 6-x+2x=3x | | 3(6y-6)-(2y+7)= | | 1.5=x*11 | | 5e-14=8 |

Equations solver categories